The TLR signalling adaptor TRIF/TICAM‐1 has an N‐terminal helical domain with structural similarity to IFIT proteins. (1st December 2013) - Ullah, M. Obayed; Ve, Thomas; Mangan, Matthew; Alaidarous, Mohammed; Sweet, Matthew J.; Mansell, Ashley; Kobe, Bostjan
<x xml:space="preserve">Abstract</x> TRIF/TICAM‐1 (TIR domain‐containing adaptor inducing interferon‐β/TIR domain‐containing adaptor molecule 1) is the adaptor protein in the Toll‐like receptor (TLR) 3 and 4 signalling pathway that leads to the production of type 1 interferons and cytokines. The signalling involves TIR (Toll/interleukin‐1 receptor) domain‐dependent TRIF oligomerization. A protease‐resistant N‐terminal region is believed to be involved in self‐regulation of TRIF by interacting with its TIR domain. Here, the structural and functional characterization of the N‐terminal domain of TRIF (TRIF‐NTD) comprising residues 1–153 is reported. The 2.22 Å resolution crystal structure was solved by single‐wavelength anomalous diffraction (SAD) using selenomethionine‐labelled crystals of TRIF‐NTD containing two additional introduced Met residues (TRIF‐NTDA66M/L113M). The structure consists of eight antiparallel helices that can be divided into two subdomains, and the overall fold shares similarity to the interferon‐induced protein with tetratricopeptide repeats (IFIT) family of proteins, which are involved in both the recognition of viral RNA and modulation of innate immune signalling. Analysis of TRIF‐NTD surface features and the mapping of sequence conservation onto the structure suggest several possible binding sites involved in either TRIF auto‐regulation or interaction with other signalling molecules or ligands. TRIF‐NTD suppresses TRIF‐mediated activation of the interferon‐β promoter, as well as NF‐κB‐dependent reporter‐gene activity. These findings thus identify opportunities for the selective targeting of TLR3‐ and TLR4‐mediated inflammation.